Bioburden in health care centers: Is the compliance with Portuguese legislation enough to prevent and control infection?. (August 2019) - Viegas, Carla; Almeida, Beatriz; Monteiro, Ana; Caetano, Liliana Aranha; Carolino, Elisabete; Gomes, Anita Quintal; Twarużek, Magdalena; Kosicki, Robert; Marchand, Geneviéve; Viegas, Susana
Abstract: This study intends to assess the bioburden in ten Portuguese health care centers (PHCC) with a multi-approach protocol using active (air sampling by impaction and impinger) and passive (surface swabs and air-conditioning filters) sampling methods, and compare the results with compliance levels of IAQ Portuguese legislation for the assessment of bioburden. The fungal burden in the PHCC was also characterized through molecular detection of toxigenic species, antifungal resistance and mycotoxins profile. Concerning legal compliance criteria for bacteriota the first criteria [indoor] + 350 CFU. m −3 < [outdoor] was not complied in all PHCC analyzed. Regarding fungal load, 60% did not comply with the quantitative guideline (I/O < 1). Growth of four fungal genera ( Chrysosporium, Cladosporium, Mucor and Penicillium ) was observed in HVAC filter samples collected from 6 out of 10 assessed PHCC when using azole-supplemented SDA media. Overall, Aspergillus / Penicillium / Paecilomyces levels were above the detection limits, except in one PHCC. The presence of mycotoxins was found both in air and HVAC filter samples. From the air samples analyzed, nine were contaminated (ng/ml) with 1–5 different mycotoxins within the same sample, whereas in HVAC filters, four samples contained 1 or 2 mycotoxins in the same filter. Overall, it was possible to conclude that Portuguese legislation is not enough to ensure IAQ in health care settings. The multi-approach sampling protocol used in this study allowed to unveil a more real scenario regarding exposure to bioburden. Detection of mycotoxins reinforces the relevance of studying mycotoxins in the clinical environment. Highlights: Portuguese legal criteria for bacteriota was not complied in all PHCC and for fungal load 60% did not comply. The presence of mycotoxins was found both in air and HVAC filter samples. Fungal biomass results have shown to be good predictors for bacterial and fungal counts in HVAC filters. The multi-approach sampling protocol used allowed to unveil a more real scenario regarding exposure to bioburden.